Sumatran orangutan diets in the Late Pleistocene as inferred from dental microwear texture analysis. (30th November 2021) - Louys, Julien; Zaim, Yahdi; Rizal, Yan; Aswan,; Puspaningrum, Mika; Trihascaryo, Agus; Price, Gilbert J.; Petherick, Ansley; Scholtz, Elinor; DeSantis, Larisa R.G.
Abstract: Orangutan ( Pongo spp.) fossils have been found throughout much of Pleistocene Southeast Asia. Today, Pongo is restricted to three living species on the islands of Borneo and Sumatra. They are predominately frugivores, and during fruit masting events their diets can consist entirely of fruit. However, food procurement strategies between masting events differ between islands and thus species. Sumatran orangutans ( Pongo abelii ) are largely able to fall back on non-masting fruit species, such as figs, such that they can maintain higher quality diets compared to their Bornean counterparts ( Pongo pygmaeus ), who ingest more lower quality and tougher foods between masting events. However, diets of fossil orangutans remain largely unknown. We investigated the diets of Sumatran orangutans from the Pleistocene deposits of the Padang Highlands, western Sumatra, using dental microwear texture analysis. We tested whether the diets of the fossil species were similar to those of Bornean orangutans, all great apes generally, and macaques that occupy similar habitats to modern orangutans, in order to gain insights into palaeoenvironments present in western Sumatra. We found that fossil orangutans consumed foods less tough than modern Bornean Pongo pygmaeus, and thus presumably more fleshy fruits (absent of significant seed mastication). We found no differences in the amount of hard object feeding between modern and fossil orangutans. Taken together, we suggest that Pleistocene orangutans from western Sumatra had similar diets to Pongo abelii, indicating that masting events were not a significant contributing factor in their intake of fruit. Finally, we suggest anisotropy values in orangutan dental microwear may be an important marker for fruit masting events in the Pleistocene.